Effects of virtual interventions based on the theory of planned behavior to improve obesity-preventive lifestyle among girls, during COVID-19 pandemic - Rafat Moghimi; Mostafa Nasirzadeh; Hassan Ahmadinia; Azizollah Pourmahmoudi; Mahdi Abdol Karimi (BMC, 2023)
Abstract Background Adolescence is a critical period for the spread of obesity and overweight. This research was conducted with the aim of determining the effect of an educational intervention based on the theory of planned behavior on promoting obesity-related behaviors in overweight female students in Gachsaran. Methods this quasi-experimental study was conducted on 90 female students of the first secondary school in the form of two intervention and control groups. Information related to nutritional status and the structures of the theory of planned behavior were collected using a researcher-made questionnaire whose validity and reliability have been confirmed. The educational intervention was carried out during five virtual training sessions. The data obtained three months after the intervention were analyzed using SPSS statistical software, version 20, using independent t-tests, paired t-tests, and equivalent non-parametric tests. Results The present study showed that the scores of the constructs of awareness, perceived behavior control, subjective norms, intention, and nutritional behaviors were significantly improved after the intervention (p < 0.001). The results of the Mann-Whitney test showed that the two intervention and control groups did not have a significant difference in terms of the average overall physical activity score after the intervention (p = 0.078). Conclusion The results of the present study showed that training based on the theory of planned behavior in the conditions of COVID-19 disease and in a virtual form had an effect on nutritional behavior but could not increase physical activity behavior in adolescents with weight loss.